PEMBELAJARAN KOSAKATA BAHASA INGGRIS MELALUI AKTIVITAS KELAS INTERAKTIF PADA PESERTA DIDIK SEKOLAH DASAR DI INDONESIA - Annamarie Febry Puarini Malelak (Journal of Education Papua Baru, 2026)
Abstract: This research reformulates a thesis-based conceptual study on English vocabulary learning for elementary schools into a publishable journal manuscript. Grounded in classroom practices at SD Muhammadiyah and a review of interactive instruction, it addresses students' difficulties in remembering basic words due to limited exposure and teacher-centered routines. The study argues that interactive classroom activities can overcome these challenges by integrating repetition, visual support, movement, peer interaction, storytelling, and digital practices. Practical strategies like picture games, word matching, word walls, vocabulary hunts, Quizizz, Educandy, and traditional games are discussed as alternatives for teachers. Literature shows that interactive activities strengthen vocabulary retention, reduce anxiety, increase participation, and connect words with communicative use. The article concludes that vocabulary teaching should be designed as a student-centered, supportive, and multisensory process rather than isolated memorization. Keywords: vocabulary acquisition; young learners; interactive classroom activities; English education; student-centered learning   Abstrak: Penelitian ini merumuskan kembali kajian konseptual berbasis penelitian mengenai pembelajaran kosakata bahasa Inggris sekolah dasar ke dalam naskah jurnal siap publikasi. Kajian ini bertolak dari praktik mengajar di SD Muhammadiyah dan telaah penelitian mengenai pembelajaran kosakata interaktif. Masalah utama yang dibahas adalah kesulitan peserta didik mengingat kata dasar akibat paparan bahasa yang terbatas dan dominasi pembelajaran berpusat pada guru. Penelitian ini menegaskan bahwa aktivitas kelas interaktif dapat menjawab persoalan tersebut melalui kombinasi pengulangan, dukungan visual, gerak, interaksi teman sebaya, storytelling, dan latihan digital. Strategi seperti permainan gambar, pencocokan kata, word wall, vocabulary hunt, Quizizz, Educandy, dan permainan tradisional dibahas sebagai alternatif praktis bagi guru. Hasil kajian menunjukkan bahwa aktivitas interaktif memperkuat retensi kosakata, mengurangi kecemasan, serta meningkatkan partisipasi peserta didik. Disimpulkan bahwa pembelajaran kosakata harus dirancang sebagai proses multisensori yang berpusat pada siswa, bukan sekadar hafalan terpisah. Kata kunci: pemerolehan kosakata; pembelajar muda; aktivitas kelas interaktif; pendidikan bahasa Inggris; pembelajaran berpusat pada siswa